Latest improvements of microchannel-plate PMTS - Lehmann, Albert; Böhm, Merlin; Miehling, Daniel; Pfaffinger, Markus; Stelter, Samuel; Uhlig, Fred; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The DIRC detectors of the P̄ANDA experiment at FAIR will use multi-anode MCP-PMTs as photon sensors. After long and extensive R&D work the performance parameters of the recent 2” MCP-PMT models are converging towards the required values. The lifetime of most ALD-coated MCP-PMTs is well surpassing the DIRC requirements with the best tube currently reaching >22 C/cm2 integrated anode charge without aging. The performance of the most advanced MCP-PMTs from PHOTONIS and Hamamatsu fulfill basically all requirements with a highlight being the high detective quantum efficiency (DQE) of almost 30% for the PHOTONIS 9002108. The improvements of the latest MCP-PMT models compared to former tubes are emphasized in this paper. In addition, some performance features of a recently developed 2” MCP-PMT by Photek Ltd are presented and discussed.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Atomic layer deposition (ALD); Cherenkov detectors; Lifetime; Microchannel-plate photomultipliers